2010
DOI: 10.1371/journal.pone.0009485
|View full text |Cite
|
Sign up to set email alerts
|

The Two Stem Cell MicroRNA Gene Clusters C19MC and miR-371-3 Are Activated by Specific Chromosomal Rearrangements in a Subgroup of Thyroid Adenomas

Abstract: Thyroid adenomas are common benign human tumors with a high prevalence of about 5% of the adult population even in iodine sufficient areas. Rearrangements of chromosomal band 19q13.4 represent a frequent clonal cytogenetic deviation in these tumors making them the most frequent non-random chromosomal translocations in human epithelial tumors at all. Two microRNA (miRNA) gene clusters i.e. C19MC and miR-371-3 are located in close proximity to the breakpoint region of these chromosomal rearrangements and have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 30 publications
2
81
0
Order By: Relevance
“…On the other hand, it has been reported that some miRNAs are located in miRNA clusters (17). Six miRNAs which we investigated were also located in two miRNA clusters, respectively.…”
Section: Discussionmentioning
confidence: 61%
“…On the other hand, it has been reported that some miRNAs are located in miRNA clusters (17). Six miRNAs which we investigated were also located in two miRNA clusters, respectively.…”
Section: Discussionmentioning
confidence: 61%
“…1) and their biological importance, as described previously (Toffanin et al 2011, Augello et al 2012. Furthermore, to get insight into deregulation of chr.19 miRNA clusters, allelic CNV of 19q13.41-42 locus (Rakheja et al 2004, Li et al 2009a, Rippe et al 2010) and the epigenetic status of C19MC promoter (Tsai et al 2009) were investigated. Importantly, our cohort comprised five matched metastatic lesions of four primitive parathyroid Ca.…”
Section: Discussionmentioning
confidence: 94%
“…Reports recently described that members of the C19MC or MIR371-3 clusters are expressed by human embryonic stem cells (hESCs; Laurent et al 2008, Li et al 2009b, Ren et al 2009) and over-expressed by human cancers (Toffanin et al 2011). Activation of both clusters might be a general phenomenon in human tumourigenesis, as rearrangements of 19q13.4, genomic amplification and methylation abnormalities including the C19MC locus have been frequently found in several human neoplasias (Li et al 2009a, Rippe et al 2010, Toffanin et al 2011. Finally, two members of the C19MC cluster, namely MIR517C and 520G, were shown to act as oncogenes, by promoting disease development in animal models (Li et al 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…Although the C19MC is silenced by promoter methylation in many cell lines, 19 it is activated together with the miR-371-373 cluster in a subgroup of thyroid adenomas, owing to chromosomal rearrangements. 48 miR-373 was identified by Agami and coworkers 28 as a potential oncogene in testicular germ-cell tumors, partly by targeting the Lats2 tumor suppressor. Later, the same group showed that it promotes breast cancer cell invasion and metastasis by targeting CD44.…”
Section: Discussionmentioning
confidence: 99%